2021
DOI: 10.29309/tpmj/2021.28.03.6009
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of liver enzyme ALT by berberis lycium in acetaminophen induced hepatic damage in mice liver.

Abstract: Objective: The objective of this research was to study the effect of Berberis lyceum (herbal plant) in reduction of liver enzyme ALT in mice. Study Design: Quasi- experimental Study. Setting: Peshawar Medical College, Peshawar. Period: December, 2016 to May, 2017. Materials & Methods: It was an experimental study which was carried out at Peshawar Medical College Warsak Road Peshawar. Total 30 (thirty) mice were used divided in six different groups with five mice in each group. After inducing hepatotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Earlier experiments have proved that Berberis lyceum protects against hepatotoxicity by bringing the liver enzymes to their normal levels. 47 Berberine which is an alkaloid present in this plant has the promising effect to reduce oxidative stress and proven beneficial against drug-induced liver toxicity. 48 A study demonstrated that berberine possesses in vivo anti-inflammatory activity and inhibits the activity of activator protein 1, which triggers inflammatory cytokines such as interleukin-6.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier experiments have proved that Berberis lyceum protects against hepatotoxicity by bringing the liver enzymes to their normal levels. 47 Berberine which is an alkaloid present in this plant has the promising effect to reduce oxidative stress and proven beneficial against drug-induced liver toxicity. 48 A study demonstrated that berberine possesses in vivo anti-inflammatory activity and inhibits the activity of activator protein 1, which triggers inflammatory cytokines such as interleukin-6.…”
Section: Discussionmentioning
confidence: 99%